PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (BPL) UNTUK MENINGKATKAN HASIL BELAJAR DAN MOTIVASI BELAJAR FISIKA SISWA KELAS X RPL 2 SEMESTER GENAP DI SMK NEGERI 1 NEGARA - Sudiatmika, I Ketut (Widyadari : Jurnal Pendidikan, 2019)
The purpose of this classroom action research is 1) increasing the students? learning outcomes and 2) improving the students? learning motivation by applying Problem Based Learning (PBL). This research was conducted on class X RPL 2 SMK Negeri 1 Negara on the even semester, year 2018/2019, with total number of students 36. This classroom action research was conducted in two cycles. The results showed that 1) the average student learning outcomes on the first cycle was 86,94, categorized as good, and the classical completeness was 100%, while on the second cycle, the average student learning outcomes was 85,07 , categorized as good,  and classical ketuntasan was 100%,  and 2) the average student learning motivation on the first cycle was 80,42, categorized as high. On the end of second cycle, the average student learning motivation was 84,94, categorized as high. The result showed that the PBL model was effective in improving Physics learning achievement and learning motivation of students of class X RPL 2 SMK Negeri 1 Negaraon the even semester, year 2018/2019.